Motives For Social Entrepreneurship Among College Students (Journal of Namibian Studies : History Politics Culture, 2023)
Teaching social entrepreneurship (SE) is important today because it has the potential to shape individuals who are more aware of their global effect. Students' drive is crucial to the success of social entrepreneurship programs. We unfortunately know very little about what drives students in Asia to become social entrepreneurs. Information on undergraduates from 16 different schools who took part in the program was compiled for this analysis. More than 300 respondents to online surveys provided usable data. The construct validity of the measuring scheme was examined with the use of a confirmatory component analysis (CFA). The findings suggested that among undergraduate students, self-efficacy was associated with an interest in formal education opportunities related to social entrepreneurship. One's degree of social support is not substantially connected with one's drive to engage in social entrepreneurship. This research significantly contributes to the fields of educational administration and entrepreneurship by expanding our understanding of the motivations of social entrepreneurs. This research has important implications for the development of public policies that aim to encourage social entrepreneurship and, by extension, to strengthen local economies and improve communities.